Controversies of Multi/Ethnic Democracy: The Case of Republic of Macedonia - Katica Kulavkova (European Scientific Journal, ESJ, 2018)
This paper aims to demystify the multi-ethnic model of the democratic form of government, which has been strongly promoted in the international political discourse toward Third World countries. In political science, this concept is actually so controversial and paradoxical, that its (pseudo) scientific use can be interpreted only as an instrument of geopolitical strategies. The author renames it "multi/ethnic democracy" to reveal that its ethnocratic and destabilizing potential overpowers its cooperative intentions. Recent empirical studies have proven the unreliability of this model, but the case study of the Republic of Macedonia has not been included yet. The combined qualitative and quantitative research in this paper shows that in the last 17 years (2001-2018) this inconsistent cross between ethnocracy and democracy in the Republic of Macedonia resulted in a series of conflicting social, political, religious, and cultural circumstances. Instead of improving the civil (trans-ethnical) concept of the state, the ethnic concept grew stronger. In a short time and with hasty constitutional revisions the former stable national and civil structure was transformed into an entropic structure full of divisions and tensions on ethnic grounds and of fragmentations and isolations on territorial, institutional, linguistic, and cultural grounds, while the existence of the Macedonian ethnos, nation, and state was brought into question.